First experimental proof of Proton Boron Capture Therapy (PBCT) to enhance protontherapy effectiveness - Cirrone, G A P; Manti, L; Margarone, D; Petringa, G; Giuffrida, L; Minopoli, A; Picciotto, A; Russo, G; Cammarata, F; Pisciotta, P; Perozziello, F M; Romano, F; et al. (Scientific reports, 2018)
Protontherapy is hadrontherapy's fastest-growing modality and a pillar in the battle against cancer. Hadrontherapy's superiority lies in its inverted depth-dose profile, hence tumour-confined irradiation. Protons, however, lack distinct radiobiological advantages over photons or electrons. Higher LET (Linear Energy Transfer) 12C-ions can overcome cancer radioresistance: DNA lesion complexity increases with LET, resulting in efficient cell killing, i.e. higher Relative Biological Effectiveness (RBE). However, economic and radiobiological issues hamper 12C-ion clinical amenability. Thus, enhancing proton RBE is desirable. To this end, we exploited the p + 11B → 3α reaction to generate high-LET alpha particles with a clinical proton beam. To maximize the reaction rate, we used sodium borocaptate (BSH) with natural boron content. Boron-Neutron Capture Therapy (BNCT) uses 10B-enriched BSH for neutron irradiation-triggered alpha particles. We recorded significantly increased cellular lethality and chromosome aberration complexity. A strategy combining protontherapy's ballistic precision with the higher RBE promised by BNCT and 12C-ion therapy is thus demonstrated.
Keywords: kombinovaná terapie; poškození DNA; sulfhydrylové sloučeniny; Fluorescent Dyes; Male; Combined Modality Therapy; Relative Biological Effectiveness; karyotypizace; Cell Line, Tumor; Alpha Particles; DNA Damage; Neutrons; chromozomální aberace; neutrony; bor; terapie metodou neutronového záchytu (bor-10); DNA nádorová; Karyotyping; lineární přenos energie; Cell Death; Proton Therapy; Prostatic Neoplasms; buněčná smrt; mužské pohlaví; izotopy uhlíku; DNA, Neoplasm; relativní biologická účinnost; Chromosome Aberrations; Dose-Response Relationship, Radiation; Animals; Linear Energy Transfer; lidé; Sulfhydryl Compounds; Humans; cyklotrony; zvířata; nádory prostaty; Carbon Isotopes; Cyclotrons; fluorescenční barviva; alfa částice; vztah dávky záření a odpovědi; protonová terapie; borohydridy; nádorové buněčné linie; Borohydrides; Boron Neutron Capture Therapy; Boron